Reconstruction of Temperature, Accumulation Rate, and Layer Thinning From an Ice Core at South Pole, Using a Statistical Inverse Method. Issue 13 (23rd June 2021) - Kahle, Emma C.; Steig, Eric J.; Jones, Tyler R.; Fudge, T. J.; Koutnik, Michelle R.; Morris, Valerie A.; Vaughn, Bruce H.; Schauer, Andrew J.; Stevens, C. Max; Conway, Howard; Waddington, Edwin D.; Buizert, Christo; et al.
Abstract: Data from the South Pole ice core (SPC14) are used to constrain climate conditions and ice‐flow‐induced layer thinning for the last 54, 000 years. Empirical constraints are obtained from the SPC14 ice and gas timescales, used to calculate annual‐layer thickness and the gas‐ice age difference (Δage), and from high‐resolution measurements of water isotopes, used to calculate the water‐isotope diffusion length. Both Δage and diffusion length depend on firn properties and therefore contain information about past temperature and snow‐accumulation rate. A statistical inverse approach is used to obtain an ensemble of reconstructions of temperature, accumulation‐rate, and thinning of annual layers in the ice sheet at the SPC14 site. The traditional water‐isotope/temperature relationship is not used as a constraint; the results therefore provide an independent calibration of that relationship. The temperature reconstruction yields a glacial‐interglacial temperature change of 6.7 ± 1.0°C at the South Pole. The sensitivity of δ 18 O to temperature is 0.99 ± 0.03 ‰°C −1, significantly greater than the spatial slope of 0.8‰°C −1 that has been used previously to determine temperature changes from East Antarctic ice core records. The reconstructions of accumulation rate and ice thinning show millennial‐scale variations in the thinning function as well as decreased thinning at depth compared to the results of a 1‐D ice flow model, suggesting influence of bedrock topography on ice flow. Key Points: An inverse method using a firn model with isotope diffusion provides self‐consistent temperature, accumulation rate, and thinning histories Glacial‐interglacial temperature change at the South Pole was 6.7 ± 1.0 K. The δ 18 O/T sensitivity is 0.99 ± 0.03 permille/K Reconstruction of ice thinning shows millennial‐scale variations in thinning function and decreased thinning at depth compared to 1‐D model